Sosialisasi Pada Siswa Smkn 5 Kota Bengkulu Untuk Membangun Literasi Di Era Digital - Anugrah, Ryandika; Damayanti, Saika; Anggrain, Jupita; Wulandari, Ewalia; Putri, Lydia Gustina; Pramita, Rice (LPPM Universitas Dehasen Bengkulu, 2026)
The rapid growth of digital technology requires students to master comprehensive digital literacy, including safety awareness, ethical communication, information verification, and productive use of digital platforms. This community service activity aimed to strengthen digital literacy among students at SMKN 5 Kota Bengkulu through structured socialization, interactive discussions, and practical demonstrations. The topics delivered included digital safety, hoax identification, social media productivity, and an introduction to artificial intelligence. The results show an increase in student understanding regarding data security, critical information assessment, ethical digital behavior, and the responsible use of AI. This activity effectively enhances students’ readiness to face technological challenges in the digital era.